Pediatric Cataract Audit at a Tertiary Care Center in Karachi - Chaudhry, Rabia Khawar; Khan, Nasar Qamar; Dembra, Weiji Kumar; Riaz, Areej; Vickash, Gaintry (Pakistan Journal of Ophthalmology, 2020)
Purpose: To perform pediatric cataract surgery audit at a tertiary care center in Karachi. Study Design: Descriptive observational study. Place and Duration of Study: From January, 2016 to July, 2018 at Ophthalmology Department of Jinnah Postgraduate Medical Center, Karachi. Material and Methods: All patients with congenital cataract were included in study regardless of presence or absence of systemic association. Patients who were lost to follow up at three months were excluded from the study. Hospital records were reviewed retrospectively and data on patient demographics, preoperative presentations, intraoperative complications and postoperative visual outcomes was documented on predesigned proformas. All patients underwent lens aspiration, posterior capsulotomy and anterior vitrectomy. Surgeries were performed under general anesthesia. Preoperative and postoperative visual acuity was assessed with ability to fix and follow light/objects, Kay picture test and Snellen’s chart according to patient’s age. Results: Three hundred and twenty six eyes underwent surgery for congenital cataract and sixty for traumatic cataract. Number of male patients was 54.93% and female was 45.07%. The average age of patients with congenital cataract was 5.01 years and that for traumatic cataract was 7.8 years. Amblyopia, nystagmus and strabismus were the commonest ocular comorbidities. Uncorrected visual acuity ranged from 6/18 to light perception preoperatively. Postoperatively 55% children with congenital cataract and 15% children with traumatic cataract had visual acuity better than 6/24. Conclusion: Early surgery in congenital cataract gives good visual outcomes. In traumatic cataract extraction, the final visual outcome depends on other effects of trauma on ocular structures.